Systematic review and meta-analysis of the effects of exercise on depression in adolescents - Xiang Wang; Zhi-dong Cai; Wan-ting Jiang; Yan-yan Fang; Wen-xin Sun; Xing Wang (BMC, 2022)
Abstract Background Depression is widespread among adolescents and seriously endangers their quality of life and academic performance. Developing strategies for adolescent depression has important public health implications. No systematic review on the effectiveness of physical exercise for adolescents aged 12-18 years with depression or depressive symptoms has previously been conducted. This study aims to systematically evaluate the effect of physical exercise on adolescent depression in the hope of developing optimum physical exercise programs. Methods Nine major databases at home and abroad were searched to retrieve randomized controlled trials (RCTs) on exercise interventions among adolescents with depression or depressive symptoms. The retrieval period started from the founding date of each database to May 1, 2021. The methodological quality of the included articles was evaluated using the modified PEDro scale. A meta-analysis, subgroup analysis, sensitivity analysis, and publication bias tests were then conducted. Results Fifteen articles, involving 19 comparisons, with a sample size of 1331, were included. Physical exercise significantly reduced adolescent depression (standardized mean difference [SMD] = − 0.64, 95% CI − 0.89, − 0.39, p < 0.01), with a moderate effect size, in both adolescents with depression (SMD = -0.57, 95% CI − 0.90, − 0.23, p < 0.01) and adolescents with depressive symptoms (SMD = − 0.67, 95% CI − 1.00, − 0.33, p < 0.01). In subgroups of different depression categories (depression or depressive symptoms), aerobic exercise was the main form of exercise for the treatment of adolescents with depression. For adolescents with depression, interventions lasting 6 weeks, 30 min/time, and 4 times/week had optimum results. The effects of aerobic exercise and resistance + aerobic exercise in the subgroup of adolescents with depressive symptoms were significant, while the effect of physical and mental exercise (yoga) was not significant. For adolescents with depressive symptoms, aerobic exercise lasting 8 weeks, 75-120 min/time, and 3 times/week had optimum results. Physical exercise with moderate intensity is a better choice for adolescents with depression and depressive symptoms. Conclusions Physical exercise has a positive effect on the improvement of depression in adolescents. The protocol for this study was registered with INPLASY (202170013). DOI number is 10.37766/inplasy2021.7.0013. Registration Date:2021.7.06.